¿Is It Just a Matter of Austerity? The Economic Crisis and Gender Equality Policies in Spain - Paleo, Natalia; Alonso, Alba (Investigaciones Feministas (Feminist Research), 2015)
Gender equality policies in Spain have experienced considerable setbacks in the last few years. The economic crisis and the need to implement austerity policies appear as the main reasons behind the huge budget-cuts and the elimination of some equality machineries. Additionally, the equality agenda has been reoriented, with maternity related issues occupying a central position. Even though these new policy priorities emerge during the crisis, they may well be related to the fact that conservative parties have taken office both at the state and the regional level. Thus, recent events invite revisiting literature on gender policies and the color of parties in government in order to explore the influence of such variable. Thanks to the analysis of all the Autonomous Communities and the central government, this article shows the impact of the presence of conservative cabinets not only in terms of a decrease of the resources dedicated to gender policies, but also in terms of the promotion of a new political agenda based on the roles of women as mothers and carers. For so doing, first, a logistic regression analysis helps capture the incidence of this variable with regard to the budgets spent by both levels of government during the period 2002-2014. Second, a qualitative analysis assesses its impact on the emergence of a new policy agenda and the shifts that have occurred in relation to the equality architecture during this same lapse of time. Consequently, this article reveals that even though most setbacks have taken place during the economic crisis, they clearly covariate with the presence of conservative parties in office. This fact allows concluding that the crisis has acted as a window of opportunity which has permitted to call into question a policy sector that had experienced a 20-year expansion period.
Keywords: Equality Policies; Spain; Economic Crisis; Political Parties.